2023
DOI: 10.3390/ijms24021494
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits and Nutrient Deficiencies in a Cohort of European Crohn’s Disease Adult Patients

Abstract: Wrong dietary habits, such as the Western-style diet, are considered important risk factors for the development of Inflammatory Bowel Diseases (IBDs). Nevertheless, the role of dietary patterns in the clinical management of IBD patients has not been fully investigated yet. Fifty-four patients diagnosed with active Crohn’s disease (CD) were enrolled and subjected to nutritional intake analysis through a weekly food diary. Nutritional patterns were analyzed, and nutrient intake was compared with those of 30 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…Internal review boards approved the studies, and patient informed consent was collected. The first cohort (BOLOGNA) was performed in the context of a 1-year prospective observational clinical trial aimed at identifying biomarkers and predictors of a failure to respond to ADA in patients with CD ( 11 ). The second cohort (PREDICROHN) was a prospective multicenter cohort study in patients with CD naïve to biologics with active luminal disease ( 12 ); participants were started on ADA and IFX and followed up longitudinally.…”
Section: Methodsmentioning
confidence: 99%
“…Internal review boards approved the studies, and patient informed consent was collected. The first cohort (BOLOGNA) was performed in the context of a 1-year prospective observational clinical trial aimed at identifying biomarkers and predictors of a failure to respond to ADA in patients with CD ( 11 ). The second cohort (PREDICROHN) was a prospective multicenter cohort study in patients with CD naïve to biologics with active luminal disease ( 12 ); participants were started on ADA and IFX and followed up longitudinally.…”
Section: Methodsmentioning
confidence: 99%
“…Active CD patients tend to adopt unbalanced nutritional patterns, while healthy eating patterns are associated with a lower risk of older-onset. 47 , 48 Mediterranean diets, rich in polyphenols and fiber, are considered a beneficial dietary regimen for IBD. 10 Low dietary fiber promotes mucin-degrading bacteria eroding healthy colon mucus, leading to lethal colitis in IL-10-deficient mice.…”
Section: Disease Pathogenesismentioning
confidence: 99%
“…Data reported in the literature mainly concern surveys on dietary habits in patients with IBD or focus on interventional studies in CD patients aimed at evaluating the effectiveness of specific dietary protocols to aid or to maintain clinical remission [ 6 ]. Our research group had already highlighted substantial differences in the nutrient intake of subjects with Crohn’s disease in comparison with healthy subjects [ 7 ]. In particular, the cross-sectional analysis of the eating habits of these patients showed that CD patients significantly reduced the consumption of fiber and vitamins (A, E, C, B6, folic acid) with respect to healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the cross-sectional analysis of the eating habits of these patients showed that CD patients significantly reduced the consumption of fiber and vitamins (A, E, C, B6, folic acid) with respect to healthy subjects. Furthermore, their calcium, potassium, phosphorus, iron, magnesium, copper, and iodine intake was significantly lower [ 7 ].…”
Section: Introductionmentioning
confidence: 99%